The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.29252/ibj.23.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cannabinoids Agonist and Antagonist in Invasion Potential of K562 Cancer Cells

Abstract: Background:The prominent hallmark of malignancies is the metastatic spread of cancer cells. Recent studies have reported that the nature of invasive cells could be changed after this phenomenon, causing chemotherapy resistance. It has been demonstrated that the up-regulated expression of matrix metalloproteinase (MMP) 2/MMP-9, as a metastasis biomarker, can fortify the metastatic potential of leukemia. Furthermore, investigations have confirmed the inhibitory effect of cannabinoid and endocannabinoid on the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“… 29 On the contrary, cannabinoid agonists induced apoptosis of PCa cells and reduced the size of tumors. 12 , 13 Additionally, several in vivo and in vitro studies revealed the crucial role of cannabinoid receptors in the anti‐proliferation of BCa cells. 27 , 30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 29 On the contrary, cannabinoid agonists induced apoptosis of PCa cells and reduced the size of tumors. 12 , 13 Additionally, several in vivo and in vitro studies revealed the crucial role of cannabinoid receptors in the anti‐proliferation of BCa cells. 27 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…Several functional studies elaborated that cannabinoids appeared to inhibit cell proliferation, migration, and angiogenesis in urological cancer cells. 11 , 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…In our experiments, we obtain a reduction in both TMBS4X gene and MMP-2 protein expression levels. While in the literature the direct effect of cannabinoids in reducing the expression of MMP-2, also attenuating invasion in leukemic cells [ 54 ], is well-documented, there are no data regarding the interaction between the TMBS4X gene and CB2 receptors. So, it could be interesting to investigate the reasons behind the reduction in gene expression after treatment with JWH-133.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, cannabinoids have been shown to inhibit cell proliferation, migration, and angiogenesis, as well as arrest the cell cycle and induce apoptosis in prostate cancer cells [ 46 ]. Furthermore, a number of in vitro studies have reported that synthetic cannabinoids such as WIN55,212, JWH-133, and JWH-015 can reduce the size of prostate cancer cell-derived tumors [ 55 , 56 ]. Of the six papers examined, five used synthetic cannabinoids [ 33 , 46 , 50 , 51 , 52 ], while the other used natural cannabinoids [ 45 ].…”
Section: Discussionmentioning
confidence: 99%